2024
DOI: 10.3389/fpls.2024.1164859
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolite profiling of Salvia rosmarinus Italian local ecotypes and cultivars and inhibitory activity against Pectobacterium carotovorum subsp. carotovorum

Valeria Iobbi,
Giuliana Donadio,
Anna Paola Lanteri
et al.

Abstract: IntroductionThe development of agriculture in terms of sustainability and low environmental impact is, at present, a great challenge, mainly in underdeveloped and marginal geographical areas. The Salvia rosmarinus “Eretto Liguria” ecotype is widespread in Liguria (Northwest Italy), and farmers commonly use it by for cuttings and for marketing. In the present study, this ecotype was characterized in comparison with other cultivars from the same geographical region and Campania (Southern Italy), with a view to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…Each 1 H NMR spectrum consisted of 64 scans, 2.05 s acquisition time, a relaxation delay (RD) of 4 s, mixing time of 0.01 s, and a spectral width of 13.33 ppm (corresponding to 8000 Hz). A pre-saturation sequence (NOESY-presat sequence, Bruker: noesygppr1d) was used to suppress the residual signal of water [110][111][112]. A Chenomx 600 MHz custom library (CCL) (Chenomx NMR Suite 8.6, Chenomx Inc., Edmonton, AB, 252 Canada) was set up by means of pure secondary metabolites obtained from commercial sources (Sigma-Aldrich, Milano, Italy).…”
Section: Nmr Spectroscopy and Processingmentioning
confidence: 99%
“…Each 1 H NMR spectrum consisted of 64 scans, 2.05 s acquisition time, a relaxation delay (RD) of 4 s, mixing time of 0.01 s, and a spectral width of 13.33 ppm (corresponding to 8000 Hz). A pre-saturation sequence (NOESY-presat sequence, Bruker: noesygppr1d) was used to suppress the residual signal of water [110][111][112]. A Chenomx 600 MHz custom library (CCL) (Chenomx NMR Suite 8.6, Chenomx Inc., Edmonton, AB, 252 Canada) was set up by means of pure secondary metabolites obtained from commercial sources (Sigma-Aldrich, Milano, Italy).…”
Section: Nmr Spectroscopy and Processingmentioning
confidence: 99%
“…Recent studies have demonstrated its potential as a preventive agent against soft rot caused by Pectobacterium carotovorum subsp. carotovorum on slices of potato tubers [122].…”
Section: Abietane Diterpenoids: Carnosic Acid and Carnosolmentioning
confidence: 99%